Educación intercultural en las escuelas: de las políticas a las prácticas en Cataluña (España) (2021)
Intercultural education is considered to be the most appropriate pedagogical model to promote inclusion, coexistence, and social cohesion both in Catalonia and in other countries. However, its philosophy is often misunderstood at the political or practical level. In this regard, this article examines the connection between national policies and what really happens in schools in Catalonia (Spain), a pioneering region in the reception of foreign students and, therefore, also a pioneer in the inclusion of intercultural discourse. Specifically, we first examine the Catalonian policies aimed at managing cultural diversity and intercultural education that have been developed since the 2000s up until today. Secondly, we present the results of a quantitative study carried out in 545 primary schools in Catalonia, in order to acknowledge the practices implemented in schools to prepare students for living in our increasingly diverse society, as well as their needs and requirements to better achieve such a commitment. Results show that whilst schools are implementing actions aimed at both fostering the integration of culturally diverse pupils as well as enhancing the intercultural competence of all students, there are still some gaps at the political level that prevent schools from developing a holistic intercultural education.